Peran Negara dalam Distribusi Keadilan di Bidang Ekonomi Menurut Pemikiran Al-Farabi - Andis Febrian; Gazali (Universitas Muhammadiyah Surabaya, 2026)
This research aims to synthesize Al-Farabi's philosophical thoughts about the concept of Al-Madinah al-Fadhilah (Primary State) and distributive justice with contemporary economic realities in Indonesia. The main focus of the study is to analyze how the principle of cooperation and the role of the state as a regulator can provide solutions to the challenges of poverty and unemployment which still experience sharp disparities between regions. This research uses a qualitative approach based on library research. The analytical descriptive method was applied to study primary sources in the form of translations of Al-Farabi's works, especially Ara Ahl al-Madinah al-Fadhilah. The research results show that poverty and unemployment in Indonesia in 2025 are indications of obstacles in the national cooperation system. Data shows structural inequality where rural poverty (11.03%) is much higher than urban (6.73%), as well as extreme poverty in the Eastern region (Central Papua 28.9%). High unemployment in industrial areas (West Java 6.77%) also indicates the state's ineffectiveness in allocating citizens' roles according to their natural talents. Collective happiness is difficult to achieve as long as the basic needs of people in remote areas are not met equally. This research provides a theoretical contribution by filling the gap in literature that connects the thoughts of Al-Farabi's classical Islamic political philosophy directly with empirical data on the Indonesian economy in 2025. The Indonesian government is advised to strengthen the state's role as the heart of economic coordination by actively intervening through inclusive fiscal policies and wealth redistribution. This research is limited to literature reviews and secondary macro data, so it does not cover micro socio-economic dynamics directly in the field.